Estimates of energy intake and expenditure in professional rugby league players - Tooley, E.; Bitcon, M.; Briggs, M. A.; West, D. J.; Russell, M.; Cheng, H. (International Journal of Sports Science and Coaching, 2015)
The nutritional and activity habits of professional Rugby League players remain unclear. Ten professional players (23±1 years, 1.85±0.02 m, 97.3±3.1 kg) recorded their dietary intake and activity habits during a competitive week including four training days (pre-match), a match day (match), and two rest days (recovery). The intake of carbohydrates (4.9±0.3 g·kg-1·d-1), proteins (2.2±0.2 g·kg-1·d-1) and fats (1.3±0.1 g·kg-1·d-1) represented 50±2%, 23±1%, and 30±1% of mean daily energy intake, respectively and a mean daily energy deficit of 947±214 KCal was estimated. Fiber intake was 26±8% lower than Recommended Nutrient Intake (RNI) values and fat intake (% energy yield) during recovery was 21±7% higher than match. Therefore, opportunities exist to optimize the diets of professional Rugby League players as fiber intake was insufficient relative to RNI values and differences between estimated energy intake and expenditure were observed. Timing throughout the competitive week also influenced dietary intake.